Pembelajaran Tahsin Al-Qur’an Metode Jibril Dalam Meningkatkan Kemampuan Membaca Pada Lansia Di Desa Nglebak - Asmi Aqidatul Izzah; Amir Muhammad Hidayatulloh (Jumat Keagamaan: Jurnal Pengabdian Masyarakat, 2022)
Nglebak village is a village which very active about the religion. Especially in reading holly Qur'an. It is proven based on observation which is conducted of inany jam'iyah (organization) in the village, like jam'iyah khotmil Qur'an , yasin and tahlil, istighosah, manaqib, and dibaiyyah. But, there are many trouble in holly Qur'an reading, there is reading law which is still wrong. The purpose of tahsin Al-Qur'an learning is to improve holly Qur'an reading skills of older people in Nglebak village, sub districk of bareng. The methot that used in this study is using jibril method technique of collecting data is using observation, pre test, and post test. To know holly Qur'an reading skills of participants before and after applied of jibril method. Tahsin Al-Qur'an learning is held for three weeks with details twice a week. It is every monday and Tuesday. And it was held on the 8 year until 29 year july 2019. At 06.00 pm. Target of this learning is the villagers of Nglebak especially in older people, with total of participants is 15 people. The result of this study have shown that there are an increase of holly qur'an reading skills to villagers, especially in the older people by using jibril method. It is we can see based on the results of pretest and post test which has been done.